2019
DOI: 10.1111/icad.12389
|View full text |Cite
|
Sign up to set email alerts
|

An insect invasion of Antarctica: the past, present and future distribution of Eretmoptera murphyi (Diptera, Chironomidae) on Signy Island

Abstract: Rising human activity in Antarctica, combined with continued warming of the polar climate, means the risk of non‐native terrestrial species colonising and establishing in its biodiversity‐ and nutrient‐poor ecosystems is increasing. Of the five non‐native invertebrate species currently in terrestrial Antarctica, the flightless midge Eretmoptera murphyi (Schaeffer, The Museum of the Brooklyn Institute of Arts and Sciences 2:90–94, 1914) is perhaps the most persistent insect invader. Accidentally introduced to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 49 publications
0
44
0
1
Order By: Relevance
“…While marine species dominate the list, key terrestrial and freshwater invertebrates were identified that could pose a threat by altering ecosystem function within this unique environment. Indeed, invertebrates have already been introduced and established on the South Orkney Islands (Signy Island) from South Georgia (Bartlett, Convey, Pertierra, & Hayward, 2019;Hughes & Worland, 2010).…”
Section: Terrestrial and Freshwater Invertebratesmentioning
confidence: 99%
“…While marine species dominate the list, key terrestrial and freshwater invertebrates were identified that could pose a threat by altering ecosystem function within this unique environment. Indeed, invertebrates have already been introduced and established on the South Orkney Islands (Signy Island) from South Georgia (Bartlett, Convey, Pertierra, & Hayward, 2019;Hughes & Worland, 2010).…”
Section: Terrestrial and Freshwater Invertebratesmentioning
confidence: 99%
“…Data in the current study were collected from three sites within 3 m of one another. As E. murphyi has a distribution of at least 80,000 m 2 over an undulating landscape [55], the environmental conditions described here may not be representative of the entire distribution range due to likely variation in snow depth, as exemplified by the difference in minimum temperatures between this study and that of Davey et al [8], despite the same locale. It is worth noting, however, that the location of the temperature loggers in this study is associated with high E. murphyi abundance [55]; thus, prior conditions are not prohibitive to survival.…”
Section: Discussionmentioning
confidence: 68%
“…The risks of establishment of invasive, nonindigenous species, under current climate change scenarios will continue to grow (e.g., in the Antarctic Peninsula Region, Ross Sea, and East Antarctic coastal areas) (Chown et al 2012a). As alien plants, invertebrates, and other taxa successfully colonize the Antarctic and sub-Antarctic, they can spread and potentially have major impacts on native ecosystems and species (Bartlett et al 2020;Hughes and Convey 2010;Hughes et al 2013Hughes et al , 2015. Individual tourist visitors to Antarctica carry more seeds on average than do governmental (science and support) personnel but, as vectors, the latter in total carry greater amounts of seeds of alien species than do tourists (Chown et al 2012a), while virtually all known introductions within Antarctica and the sub-Antarctic in recent decades (i.e., after the era of marine exploitation) are far more plausibly associated with national operator activities than those of the tourism industry (Frenot et al 2005).…”
Section: Biological Invasionsmentioning
confidence: 99%
“…For example, the presence of balanomorph barnacles and live individuals of the cosmopolitan pelagic barnacle, Conchoderma auritum, demonstrated the potential for non-native species to be transported to Antarctica this way (Hughes and Ashton 2017). Increasingly, modeling approaches are being used to predict potentially wide ranging future changes in distribution of both native and non-native terrestrial species in Antarctica (Bartlett et al 2020;Contador et al 2020;Hughes et al 2019;Pertierra et al 2017Pertierra et al , 2020.…”
Section: Biological Invasionsmentioning
confidence: 99%